Liquidity Management in Islamic Banking: Issues and Challenges - Siti Kholifatul Rizkiah (Tazkia Islamic Finance and Business Review, 2018)
As a financial intermediation, banking industry has and will always be bound with mismatch maturity problem between asset and liabilities which leads to liquidity issue. This article uses a literature study to observe the current liquidity trend in Islamic banking, the issues faced by the existing Islamic liquidity instruments and ways to overcome it. It is found that the common issues associated with Islamic liquidity instruments are sharia issue, inactivity of its secondary market, key issues on short term sukuk issuance and difficulty of cross-border transactions. A better management on liquidity position and a more robust liquidity infrastructure are needed for a better liquidty management in Islamic banking industry.